World Bank Economists' Forum (volume 2) (The World Bank, 2002)
This volume evaluates some of the key dimensions of human development and growth. It provides eight exceptional papers from the second World Bank Economists' Forum held in May 2001 in Washington, DC. These papers were selected from among the 46 papers presented at the Forum. Many of those selected concentrate on the issues surrounding "empowerment." The focus is upon ensuring that poor people have the education, health care, social protection, and other mechanisms necessary for them to participate in economic growth and social development